Perspectives on the Late Piano Music of Oskar Morawetz and John Weinzweig - Keillor, Elaine (Intersections, 2013)
Oskar Morawetz and John Weinzweig were colleagues of Carl Morey at the Faculty of Music, University of Toronto. Each composed considerable piano music throughout his compositional career. In this article, the author examines the late piano compositions of Morawetz and Weinzweig, comparing approaches to the instrument, and how those approaches were reflected musically in this group of late compositions. Because Morawetz based his approach on the late Romantic piano compositions with which he was familiar, pianists do not encounter extended techniques in his works. Weinzweig, on the other hand, makes new demands upon the performer to bring across his “disparate gestic/phonetic shapes.”